1986
DOI: 10.1210/endo-119-5-2106
|View full text |Cite
|
Sign up to set email alerts
|

Steroids and the Secretory Function of the Exocrine Pancreas*

Abstract: The influence of steroids on the exocrine pancreas of male rats was examined by removing steroid producing tissue and by introducing individual steroids into these animals at a later date. Castration had no demonstrable morphological effect on acinar cells, whereas castration combined with adrenalectomy caused a marked depletion of zymogen granules as well as widening of peri- and interlobular spaces. Treatment of castrated-adrenalectomized rats with estradiol restored a normal appearance of the pancreas withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…This is indicated by a good correlation between GGT and digestive enzyme outputs during stimulation (2). An alternative mechanism is that the newly added ZG membrane, bearing GGT, mixes with the apical membrane and is subsequently shed when microvilli fragment into pancreasomes in the lumen (6). These mechanisms are not mutually exclusive and probably operate concomitantly.…”
Section: Discussionmentioning
confidence: 99%
“…This is indicated by a good correlation between GGT and digestive enzyme outputs during stimulation (2). An alternative mechanism is that the newly added ZG membrane, bearing GGT, mixes with the apical membrane and is subsequently shed when microvilli fragment into pancreasomes in the lumen (6). These mechanisms are not mutually exclusive and probably operate concomitantly.…”
Section: Discussionmentioning
confidence: 99%
“…Electron Microscopy-Cell pellets and pieces of pancreas tissues were processed for electron microscopy as described previously (4).…”
Section: Methodsmentioning
confidence: 99%
“…Possible clues for the elucidation of these processes come from experiments which reported that adrenalectomy of male rats caused a marked depletion of ZG in the pancreas acinar cells, an effect which was reversed by treatment with the synthetic glucocorticoid, triamcinolone (3,4). It was also found that a dexamethasone treatment of the AR42J rat pancreatic cells induces the appearance of ZG (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals as well, the pancreas binds gonadal hormones, and absorbs more sexual steroid hormones than classical target tissues such as the prostate gland [1]. Boctor et al [2] detected specific estradiol-binding proteins in the pancreas of rats and Beaudoin et al [3] demonstrated estradiol-induced changes in both the enzyme secretion and the pancreas histology (indicating reduced secretion). Previous evidence that estradiol had a stimulatory effect on cellular trypsinogen production in fish [4] as well as the presence of estradiol receptors in the exocrine pancreas [5] led us to investigate the effect of estradiol on pancreatic cells.…”
Section: Introductionmentioning
confidence: 99%